PTU-260 Pcr and toxin eia in diagnosing and predicting outcome of clostridium difficile infection in an island population. (22nd June 2015) - Kumar, S; Pollok, R; Muscat, I; Planche, T
Abstract : Introduction: Clostridium difficile infection (CDI) can be life-threatening, with an estimated mortality of up to 15%. The clinical significance of a positive PCR test in CDI remains unclear. We compared clinical characteristics, inflammatory markers and mortality in CD toxin positive patients with toxin negative, PCR positive individuals. We also aimed to identify risk factors associated with the development of toxin positive CDI. Method: A retrospective case-control study was conducted at the Jersey General Hospital of patients who developed CDI between 2008 and 2012. For each toxin positive case, 2 age/sex/ward/period-matched controls without diarrhoea were selected randomly. 131 toxin negative, GDH positive samples had PCR using Cepheid Xpert. Patient demographics, clinical characteristics and 30 day case-fatality rate were collated. Results: During the study, 207 patients were toxin positive, 92 PCR positive and toxin negative and 39 had a stool sample negative by both toxin and PCR testing. A positive toxin EIA stool sample was associated with both significantly higher WCC (14.5 × 10 9 /L versus 11.3 × 10 9 /L, p = 0.003) and CRP (114.7 mg/dL versus 82.9 mg/dL, p = 0.001) but PCR positivity was not (p > 0.05). A positive toxin EIA test was a significant independent predictor of death (OR: 1.89 [95% CI: 1.0–3.4], p = 0.046) but a positive NAAT in the absence of EIA-detectable toxin was not (OR: 1.0 [95% CI: 0.3–3.1], p = 1.0). Multivariate analysis demonstrated that alcoholic/liver disease (p = 0.042), urinary tract infection (p = <0.0001), gastrointestinal disease (p = 0.001), exposure to antimicrobial therapy (p = <0.0001) and acid supression (p = <0.0001) in the previous 28 days were significantly associated with the development of toxin positive CDI. Amoxicillin, benzylpenicillin, carbapenem, cefalexin, ciprofloxacin, co-amoxiclav, gentamicin, vancomycin and metronidazole were associated with the development of toxin positive CDI. Conclusion: In toxin negative CDI, PCR neither predicts disease severity nor mortality. However, it may have a role in disease surveillance and infection control. Judicious use of antibiotics and PPIs can play an important role in the prevention of CDI. Disclosure of interest: None Declared.